Transcatheter dilation and stenting of the modified blalock-taussig shunt in cyanotic heart diseases: points to consider. A single-center experience - Mini, Nathalie; Zartner, Peter A.; Schneider, Martin B. E. (Frontiers in Cardiovascular Medicine, 2024)
Background Our study focuses on the technique and results of interventional dilation and stenting of the modified Blalock–Taussig shunt (MBTS) performed in our center, providing a comprehensive review of our practice over the past 4 years. Methods 42 catheter interventions on MBTS performed on 32 patients between January 2020 and May 2024 included 11 balloon dilatations and 31 stenting procedures. They were analyzed retrospectively. We documented early and late complications, the need for in-shunt reintervention or surgical revision, in-stent thrombotic events, and sudden death. Results The median age, weight, body surface area, and procedural radiation time at the time of the intervention were 100 days (15–870 days), 5 kg (2.6–12 kg), 0.3 m2 (0.19–0.54 m2), and 12 min (7–28 min). Four interventions were performed as an emergency in three patients, of which three were performed with ECMO support. The interventions were semi-emergent for severe hypoxia in 22 patients and elective for mild desaturation in the rest. All interventions were successfully performed without any intervention-related complications or death. Eighty-two percent of the shunt dilations led to saturation improvement. Of the 31 shunt stentings performed in 26 patients, saturation improvement was documented in 97% of the cases. The late complication with stent thrombosis was documented in one patient. In two patients, sudden death and cardiac decompensation with the need for resuscitation were documented. Conclusion MBTS interventions are effective in emergent and semi-emergent situations with severe hypoxia. While serial balloon dilatations improved the luminal diameter in clipped MBTS, most patients needed stenting as a definitive procedure. In some cases, enlargement of the shunt via stenting may be an alternative to the surgical shunt revision to accommodate the shunt size and weight and delay the subsequent operation when there are contraindications. Dual antiplatelet therapy is strongly recommended to reduce thrombotic events, especially in shunts with more than one stent and those that need reinterventions.